Phosphorylation of Shrimp Tcf by a Viral Protein Kinase WSV083 Suppresses Its Antiviral Effect - Wang, Chuanqi; Ruan, Lingwei; Shi, Hong; Lin, Wenyang; Liu, Linmin; Li, Sujie (Frontiers in Immunology, 2021)
Nuclear DNA-binding TCF proteins, which act as the main downstream effectors of Wnt signaling, are essential for the regulation of cell fate and innate immunity. However, their role during viral infection in shrimp remains unknown. Herein, we demonstrated that Litopenaeus vannamei TCF (LvTcf) acts independently of Lvβ-catenin to promote interferon-like protein LvVago1 production, thus mounting the response to WSSV infection. Further, we observed that WSV083, a WSSV serine/threonine protein kinase, bound to LvTcf and phosphorylated it. Phosphorylated LvTcf was then recognized and degraded via the ubiquitin-proteasome pathway. Moreover, mass spectrometry analyses indicated that the T39 and T104 residues of LvTcf were target sites phosphorylated by WSV083. Point mutation analyses suggested that additional sites of LvTcf may undergo phosphorylation via WSV083. Taken together, the current work provides valuable insights into host immunity and viral pathogenesis. LvTcf is not only a modulator of shrimp innate immunity but is also an important target for WSSV immune evasion. Thus, the current findings will help improve disease control in shrimps.